Kerusakan Lingkungan Hidup pada Ekosistem Ditinjau Berdasarkan Hukum : (Studi Kasus Kerusakan Lingkungan Hidup oleh PT. DPM Dairi) - Taufiq Ramadhan; Johan Pardamean Simanjuntak; Linton Naibaho; Kania Nova Ramadhani; Agung Torang Sitohang; Desy Yolanda Br Bangun; Johana Andriani Nainggolan; Nazlah Aulia; Nelly Moria Hutapea; Roselli Anjelina Lumbansiantar (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Environmental damage carried out by PT DPM Dairi is considered a violation of Law Number 32 of 2009 concerning Environmental Protection and Management. As a result of environmental damage caused by PT DPM Dairi, especially in zinc mineral mining, it can severely damage the surrounding ecosystem. The objectives of this research are, To Know and examine the consequences of environmental damage carried out by PT DPM Dairi. How the Government Efforts to Find Solutions Due to Environmental Damage by PT.DPM Dairi. This research uses a normative juridical method, which is done by tracing legislation and library materials which are then written descriptively. The community succeeded in canceling PT.DPM Dairi's license. The facts of the trial showed that the existence of the mine in a disaster-prone area right above the North Sumatra earthquake fault threatened the safety of more than 300 thousand